Aplikasi Video Edukasi “Dispepsia“ melalui Media Sosial - Hesti Marliza; Sri Hainil; Delladari Mayefis; Suci Fitriani Sammulia (LPPM STIKES Guna Bangsa Yogyakarta, 2022)
Dyspepsia is not a life-threatening case but the symptoms of the disease occur for a long time. Dyspepsia has a strong impact on health-related quality of life because the natural course of dyspepsia is chronic and often recurs, and the administration of therapy is less effective in controlling symptoms. Symptoms of dyspepsia can interfere with daily activities, and result in a significant impact on quality of life and increased medical costs. Providing education is used as an alternative so that people can understand the type of gastric disease they are suffering from. But in fact, the education provided can be a source of medication errors, due to a lack of public knowledge about dyspepsia. Providing appropriate information can protect the public from the dangers of dyspepsia, therefore providing education about dyspepsia through social media is considered the most effective way, especially during the current pandemic. The purpose of this activity is to educate the public about dyspepsia. The method used in this activity is to use educational videos that are distributed through social media. The results of this activity are responses from the general public who are active on social media who watch educational videos that have been distributed, almost all of the responses given are in the form of comments saying that this educational video is very useful. The conclusion of this activity is that the use of social media is considered capable of providing education to the public regarding dyspepsia.